Answer:
The third force = [tex]-(26.0 \, N \, \hat{i} + 12.00 \, N \, \hat{j})[/tex]
Explanation:
Here we note that, the formula for the resultant force is as follows;
[tex]\Sigma F = \Sigma F_x + \Sigma F_y[/tex]
Also
∑F = m×a
Where:
[tex]F_x[/tex] = Force components in the x direction
[tex]F_y[/tex] = Force components in the y direction
∑F = Resultant force vector
m = Mass of the object
a = Acceleration vector ob the object =
[tex]a = 8.00 \, m/s^2 \, \hat{i} + 6.00 \, m/s^2 \, \hat{j}[/tex]
[tex]F_1 = 30.0 \, N \, \hat{i} + 16.0 \, N \, \hat{j}[/tex]
[tex]F_2 = 12.0 \, N \, \hat{i} + 8.00 \, N \, \hat{j}[/tex]
Therefore, since ∑F = m×a, we have;
[tex]\Sigma F = 2 kg \times (8.00 \, m/s^2 \, \hat{i} + 6.00 \, m/s^2 \, \hat{j})[/tex]
[tex]\Sigma F = (16.00 \, m/s^2 \, \hat{i} + 12.00 \, m/s^2 \, \hat{j})[/tex]
Hence from [tex]\Sigma F = \Sigma F_x + \Sigma F_y[/tex], we have;
[tex]F_{x1} + F_{x2} + F_{x3} = 16[/tex]
That is 30 + 12 + [tex]F_{x3}[/tex] = 16
∴ [tex]F_{x3}[/tex] = 16 - (30 + 12) = -26
Similarly,
[tex]F_{y1} + F_{y2} + F_{y3} = 12[/tex]
Therefore, [tex]F_{y3}[/tex] = 12 - (16 + 8) = -12
Hence, [tex]F_3 = -26.0 \, N \, \hat{i} - 12.00 \, N \, \hat{j} = -(26.0 \, N \, \hat{i} + 12.00 \, N \, \hat{j})[/tex]
The third force, [tex]F_3, = -(26.0 \, N \, \hat{i} + 12.00 \, N \, \hat{j})[/tex]